2011 37th IEEE Photovoltaic Specialists Conference 2011
DOI: 10.1109/pvsc.2011.6186266
|View full text |Cite
|
Sign up to set email alerts
|

Testing of solar cells for the Solar Probe Plus mission

Abstract: The Solar Probe Plus (SPP) is an upcoming mission in NASA's "Living with a Star Program" to be built by the Johns Hopkins University Applied Physics Laboratory. The spacecraft will orbit the sun for a primary mission duration of seven years, making a closest approach to the sun at a distance of 0.0442 AU. Instrumentation on SPP will focus on two primary science investigations: the sun's coronal heating and solar wind acceleration, and the production, evolution, and transport of solar energetic particles. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Most investigations focus on space irradiations in HEO such as thermal cycling, proton and electron, and UV, and less attention has been paid on the characterization and mechanism of the device degradation caused by space irradiations. [ 13,50 ]…”
Section: Resultsmentioning
confidence: 99%
“…Most investigations focus on space irradiations in HEO such as thermal cycling, proton and electron, and UV, and less attention has been paid on the characterization and mechanism of the device degradation caused by space irradiations. [ 13,50 ]…”
Section: Resultsmentioning
confidence: 99%
“…After a review of the available literature, the first example found in relation to spacecraft solar array testing is the SERT II mission, which was carried out by using lamps [16]. It seems that within the space industry, the testing of solar cells is carried out after qualification testing [17], environmental exposure degradation testing [18], or by studying solar array performance under special environmental conditions such as close-to-the-Sun or far-from-the-Sun missions [19,20]. Obviously, missions in which new photovoltaic technologies are used require thorough testing campaigns, carried out by using sunlight simulators [21].…”
Section: Introductionmentioning
confidence: 99%